Numerical investigation of electro-conjugate fluid micro-pump under the effects of downstream angle and the negative electrode width - Do, Van Tran; Lai, The Khanh; Vu, Toan Thang; Nguyen, Thi Anh; Ngo, Ich Long (Vietnam Journal of Mechanics, 2025)
This paper describes a numerical study of the electro-hydrodynamic behaviors of the fluid flow in an electro-conjugate fluid (ECF) micro-pump under the effects of the collector electrode width (Lc) and its downstream angle (α2). The finite element method was used to examine the characteristics of the ECF micro-pump with the applied voltage ranging from 2 kV to 8 kV, Lc ranging from 0.0 to 4.0, and α2 ranging from 30º to 90º. Consequently, the numerical results indicated that the ECF flow characteristics and the operating ranges of this ECF micro-pump are affected significantly by α2 and Lc of the negative electrode. Indeed, the operating range of the ECF micro-pump can be further extended by reducing α2, particularly at higher flow rates. Moreover, the operating ranges of both pressure difference (∆p) and flow rate of the ECF micro-pump can be extended when Lc varies in the optimum range, i.e., from 0.5 to 2.0. The maximum efficiency of such an ECF micro-pump was 7.4% at φ0 = 8 kV and Lc = 2.0. These results play a critical role in understanding the electro-hydrodynamic behaviors of the fluid flow in an ECF micro-pump, and they can be applied in mechanical and biomedical engineering fields.